ANALISIS PEMBERIAN REWARD AND PUNISHMENT KEPADA PESERTA DIDIK DI SD INPRES1 BALINGGI - Puspaeni, Ni Luh Dewi; Anta, I Made Nuhari; Sudarsana, Wayan (STAH Dharma Sentana Sulawesi Tengah, 2024)
This research aims to analyze the provision of rewards and punishment to students at SD Inpres 1 Balinggi. The method used in this research is descriptive qualitative method. The research results obtained through interviews and also using an observation sheet guide show that there are several forms of reward and punishment applied at SD Inpres 1 Balinggi. Forms of reward include: verbal reward (reward in the form of speech) such as